LGG-47. CARBOPLATIN AND VINBLASTINE THERAPY FOR PEDIARIC LOW-GRADE GLIOMA. Issue 2 (22nd June 2018) - Nellan, Anandani; Wright, Erin; Hemenway, Molly; Raybin, Jennifer; Foreman, Nicholas; Rush, Sarah; Dorris, Kathleen
Abstract: BACKGROUND: Low grade gliomas (LGG) represent the most common pediatric central nervous system tumor. LGG therapy usually involves surgical resection; when total resection is not feasible, management strategies may include chemotherapy. Multiple pediatric LGG chemotherapy regimens have been investigated with variable 2-year progression free survival (PFS) rates of 39-68%. To date, treatment of pediatric LGG with a carboplatin and vinblastine chemotherapy regimen has not been fully evaluated. METHODS: A retrospective review of pediatric patients with LGG treated with carboplatin and vinblastine (C/VBL) at Children's Hospital Colorado and Akron Children's Hospital from 2011-2017 was conducted. Data collected included patient demographics, tumor location/response, neurofibromatosis status, C/VBL duration and toxicities. RESULTS: Thirty-five patients (24:11; males:females) were identified for analysis; 29 patients were treated with C/VBL as upfront therapy; six at disease progression. The majority of the patients had tumors in the optic pathway/hypothalamic region (46%). Four patients had multifocal disease at diagnosis. Five patients had neurofibromatosis type 1 (NF1). BRAF alterations were identified in 12/20 tested patients. The median age at start of therapy was 6.32 years (range, 0.55-17.66 years). Best therapy response was partial response in 4 patients and stable disease in 22 patients. Nine patients progressed during therapy. Two-year PFS rates were 51% (all patients), 60% (NF1 patients) and 49% (non-NF1 patients). Only four patients experienced delays in C/VBL therapy due to cytopenias, and 10 febrile neutropenia admissions were noted. CONCLUSION: This experience suggests that C/VBL achieves similar PFS rates to other investigated chemotherapy regimens for pediatric LGG with minimal toxicities.